Encefalopati uremikum pada pasien gagal ginjal: Laporan kasus - Pratiwi Hendro Putri; Dea Rahma Kustiwa; Wina Carolina; Yolanda Rosa; Faramitha Sandra; Jauhari Jauhari; Aris Aris (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2024)
Background: Patients with kidney failure often experience clinical symptoms related to fluid and electrolyte imbalance, anemia, malnutrition, and gastrointestinal disorders. One of the complications of kidney failure is Uremic Encephalopathy (UE). Uremic encephalopathy is an organic brain disorder that occurs in patients with acute or chronic kidney failure. Usually the creatinine clearance level decreases and remains below 15 mL/minute. Purpose: To discuss aspects of definition, epidemiology, etiology and risk factors, classification, pathophysiology, diagnosis, management, complications and prognosis of metabolic encephalopathy, especially metabolic encephalopathy (uremicum). Method: The case study research design is a research method that uses various data sources that can be used as research material, describing and explaining comprehensively various aspects of an individual, group, program, organization or event systematically. Case studies can be applicable when a how and why question is asked about a set of present events that are impossible or at least difficult to control. This case study is a study to explore the problem of nursing care for clients with nursing care for patients suffering from uremic encephalopathy. Results: A patient named Mrs. 73 year old S came to the emergency room at Jend. Ahmad Yani Metro Regional General Hospital on September 22 2023, was accompanied by his family with the main complaint of difficulty swallowing. Due to the patient's complaints of difficulty swallowing, the patient had difficulty eating and drinking. Complaints accompanied by slurred speech and weakness in left limbs since ± 10 days before entering the emergency room at General Ahmad Yani Metro Hospital. The patient's family said that the patient was difficult to communicate with and the patient was always anxious. There is a history that 2 months ago the patient experienced a similar complaint, namely weakness in the left limb. Then the family also stated that the patient had a history of kidney failure which was only discovered about 1 month ago, a history of diabetes mellitus and hypertension. Due to the patient's complaints of difficulty swallowing, the patient had difficulty eating and drinking. On physical examination, decubitus ulcers were found on the buttocks. Motor function examination revealed weakness of the left limb. From the CT-Scan supporting examination, there was an infarction in the corona radiata dextra and cerebral atrophy. Furthermore, the results of the thorax X-ray examination showed that the lungs were normal, the cast showed cardiomegaly and the elongation of the aorta was suggestive of HHD. Conclusion: Uremic Encephalopathy (UE) is a clinical syndrome without definite diagnostic criteria. These patients may exhibit nonspecific signs and symptoms such as fatigue, anorexia, nausea, and confusion. The clinical picture is variable, and other diagnoses should be considered, such as hypertensive encephalopathy, hyperosmolar coma, metabolic encephalopathy, and drug toxicity. Keywords: Hypertension; Kidney failure; Uremic Encephalopathy. Pendahuluan: Pasien dengan gagal ginjal sering mengalami gejala klinis yang berkaitan dengan ketidakseimbangan cairan dan elektrolit, anemia, malnutrisi, dan gangguan gastrointestinal. Salah satu dari komplikasi gagal ginjal tersebut adalah Uremic Encephalopathy (UE). Uremic encephalopathy adalah kelainan otak organik yang terjadi pada pasien dengan gagal ginjal akut maupun kronik. Biasanya dengan nilai kadar creatinine clearance menurun dan tetap dibawah 15 mL/menit. Tujuan: Untuk membahas aspek definisi, epidemiologi, etiologi dan faktor resiko, klasifikasi, patofisiologi, diagnosis, tatalaksana, komplikasi dan prognosis ensefalopati metabolik, khususnya ensefalopati metabolik (uremikum). Metode: Rancangan penelitian studi kasus yakni metode riset yang menggunakan berbagai sumber data yang dapat digunakan sebagai bahan riset, menguraikan, serta menjelaskan secara komprehensif berbagai aspek individu, kelompok, suatu program, organisasi, atau peristiwa secara sistematis. Studi kasus dapat berlaku apabila suatu pertanyaan bagaimana dan mengapa diajukan terhadap seperangkat peristiwa masa kini yang mustahil atau setidaknya sulit untuk dikontrol. Studi kasus ini adalah studi untuk mengeksplorasi masalah asuhan keperawatan pada klien asuhan keperawatan pada pasien penderita uremic encephalopathy. Hasil: Seorang pasien bernama Ny. S berusia 73 tahun datang ke IGD RSUD Jend. Ahmad Yani Metro pada tanggal 22 September 2023, diantar oleh keluarganya dengan keluhan utama sulit menelan. Dikarenakan keluhan sulit menelan yang dialami pasien, pasien kesulitan makan dan minum. Keluhan disertai bicara pelo dan lemah anggota gerak sebelah kiri sejak ± 10hari lalu sebelum masuk IGD RSUD Jenderal Ahmad Yani Metro. Keluarga pasien mengatakan bahwa pasien sulit diajak komunikasi dan pasien selalu gelisah. Terdapat riwayat bahwa 2 bulan lalu pasien mengalami keluhan serupa yaitu lemah anggota gerak sebelah kiri. Kemudian keluarga juga menyatakan bahwa pasien mempunyai riwayat gagal ginjal yang baru diketahui sekitar 1 bulan yang lalu, riwayat penyakit diabetes melitus dan hipertensi. Dikarenakan keluhan sulit menelan yang dialami pasien, pasien kesulitan makan dan minum. Pada pemeriksaan fisik ditemukan ulkus dekubitus di bagian bokong. Pemeriksaan fungsi motorik ditemukan kelemahan anggota gerak sebelah kiri. Dari pemeriksaan penunjang CT-Scan terdapat infark di corona radiata dextra dan Atrofi cerebri. Selanjutnya, pada hasil pemeriksaan Rontgen thorax terkesan pulmo normal, cor terkesan cardiomegali dan elongati oaortae sugestif HHD. Simpulan: Uremic Encephalopathy (UE) adalah sindrom klinis tanpa kriteria diagnostik yang pasti. Pasien-pasien ini mungkin menunjukkan tanda dan gejala yang tidak spesifik seperti kelelahan, anoreksia, mual, dan kebingungan. Gambaran klinisnya bervariasi, dan diagnosis lain harus dipertimbangkan, seperti ensefalopati hipertensi, koma hiperosmolar, ensefalopati metabolik, dan toksisitasobat.